A curved triangular element for nonlinear analysis of laminated shells - Rezaiee-Pajand, M.; Arabi, E. (Composite structures, 2016)
A brief review of the laminated shell analyses is presented. The related literatures demonstrate that most previous studies deal with the quadrilateral or flat triangular elements and not the curved triangular element. Based on the continuum mechanic’s theory, a 6-node triangular isoparametric element is formulated for geometrically nonlinear analysis of laminated shells. To prevent the membrane and shear locking effects, the suggested scheme uses assumed strains for in-plane and transverse shear strains. Large displacements and rotations in the nonlinear analysis are included via the total Lagrangian description. Several popular benchmark problems are solved by the Generalized Displacement Control Method. The numerical results obtained are in good agreement with those published by other investigators.